The white concentration camps of the Anglo-Boer War: A debate without end (Historia, 2021)
From time to time the debate on white and black concentration camps in the Anglo-Boer War of 1899-1902 flares up, and it seems that there is no end in sight. In the past three to four decades the discussion on the black camps that have been undisclosed for so long has come to the fore, which in itself sheds a very interesting light both on the suffering of black people in the Anglo-Boer War and the political and historiographical climate of the period in which they are studied. The battle lines are, however, still drawn from time to time on the white camps, and the writings of Afrikaner and English-speaking (both South African and British) historians still persist in presenting viewpoints that range from attempts at objectivity to blatant subjectivity and plain bad history.
Keywords: Afrikaner nationalism; Anglo-Boer War; British Blue Books; concentration camps; Elizabeth van Heyningen; Emily Hobhouse; E. Neethling; Liz Stanley; post/memory; sanitation; Afrikaner-nasionalisme; Anglo-Boereoorlog; Britse Blouboeke; konsentrasiekampe; sanitasie